2021
DOI: 10.1007/s40747-021-00328-7
|View full text |Cite
|
Sign up to set email alerts
|

3D-semantic segmentation and classification of stomach infections using uncertainty aware deep neural networks

Abstract: Wireless capsule endoscopy (WCE) might move through human body and captures the small bowel and captures the video and require the analysis of all frames of video due to which the diagnosis of gastrointestinal infections by the physician is a tedious task. This tiresome assignment has fuelled the researcher’s efforts to present an automated technique for gastrointestinal infections detection. The segmentation of stomach infections is a challenging task because the lesion region having low contrast and irregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 61 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…They applied a modified residual neural network by changing the kernel size for the detection of the knee joint and then combined it with convolutional (BAM) to achieve multi-class accuracy of 74.8%. This method also needs to improve the classification accuracy [ 43 ]. Kondal et al [ 55 ] used two datasets, one from OAI, which has 4447 DICOM format images with their KL grades for training, and the second dataset is from an Indian private hospital having 1043 knee radiographs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They applied a modified residual neural network by changing the kernel size for the detection of the knee joint and then combined it with convolutional (BAM) to achieve multi-class accuracy of 74.8%. This method also needs to improve the classification accuracy [ 43 ]. Kondal et al [ 55 ] used two datasets, one from OAI, which has 4447 DICOM format images with their KL grades for training, and the second dataset is from an Indian private hospital having 1043 knee radiographs.…”
Section: Resultsmentioning
confidence: 99%
“…There has been plenty of work carried out in the area of KOA imaging to identify and classify knee diseases. In image processing, feature extraction is an effective step for image representation [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. For the recognition of diseases, feature extraction is very helpful to machine learning (ML) algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Efficient classification based on automatic feature extraction is prepared by a convolutional neural network [22,[45][46][47][48][49][50]. Deep learning [19,20,43,48,51,52] methods are pre-trained models like AlexNet, GoogleNet [53], ResNet [54], VGG-16 [33], Inception V3 [55], and many others are used as feature extractors and feature selector. Ahmed et al suggested a method of WBCs feature extraction using a powerful CNN architecture VGGNet, extracted features are then filtered by the simulation of electron spectra for surface analysis (SESSA) algorithm [56].…”
Section: Related Workmentioning
confidence: 99%
“… 25 , 26 , 27 , 28 , 29 Using computer‐aided diagnostic systems high accuracy of disease detection has been achieved. 30 , 31 , 32 , 33 Machine learning (ML)‐based diagnosis mechanisms are gaining increased attention in the many fields. 34 , 35 , 36 , 37 , 38 Medical diagnostic systems are being automated with help of deep learning (DL) that is an advanced version of ML and is a subset of AI.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in computing technology, specifically in artificial intelligence (AI) and medical image processing, make it possible to detect many diseases automatically 25–29 . Using computer‐aided diagnostic systems high accuracy of disease detection has been achieved 30–33 . Machine learning (ML)‐based diagnosis mechanisms are gaining increased attention in the many fields 34–38 .…”
Section: Introductionmentioning
confidence: 99%